Design and development of a stair climbing baby stroller - Kokkinos, Nicholas; Chatzigeorgiou, Georgios (My University, 2025)
This research critically examines the conceptualisation and prospective fabrication of a novel baby stroller designed to ascend/descend staircases with considerably less exertion relative to conventional models. A staged methodology is advanced that begins with structured ideation and concept screening, progresses through CAD based three-dimensional modelling and finite element analysis (FEA) simulations, and culminates in preliminary market evaluation and pricing analysis. By integrating a specialized wheel assembly with a structurally optimized frame, the proposed design seeks to improve mobility for caregivers in complex urban terrains while satisfying cost effectiveness and manufacturability constraints.
Keywords: novel baby stroller; ascend/descend staircases; καινοτόμου παιδικού αμαξιδίου; συμβατικά μοντέλα